Therapy of Gouty Arthritis in Obese Patients Using Cryopreserved Placental Extract - Yurchenko, Tatyana N.; Kapustyanskaya, Anna A.; Shepitko, Vladimir I. (Problems of Cryobiology and Cryomedicine, 2013)
The data about prevalence of a gout combined with obesity inUkraineare demonstrated in the research. In clinics (107 patients) we compared the outcomes of gouty arthritis therapy applying the standard protocol and the combination involving cryopreserved human placental extract (CHPE). Twelve months following treatment a positive effect of CHPE administration was revealed in the disease course: the reduction of a number and duration of arthritis attacks by 28.57%; decrease in pain index from 9.8 (prior to treatment) down to 1.4 point; content of uric acid from 768.0 down to 358.1 mmol/l; erythrocyte sedimentation rate from 35.5 down to 14.0 mm/hr; and content of C-reactive protein from 13.0 down to 4.5 mg/l. Following standard therapy these indices were, correspondingly, 14.28%; 2.8 points; 419.3 mmol/l; 18.00 mm/hr and 5.1 mg/l. Probl Cryobiol Cryomed 2013; 23(4):326–337.